Understanding the European sentiment towards a Tax-Based Universal Basic Income - Alm Ramberg,Erik (2025)
The study is an empirical analysis of what drives the sentiment towards a tax-funded Universal Basic Income (UBI) implementation in 12 European countries, both on an individual and country level. The two core research questions are: How do the subjective perceptions of household income influence the sentiment towards the implementation of a basic income scheme on an individual level? and how does income inequality influence the individual and mean national sentiment towards the implementation of a basic income scheme? The analysis is based on survey data from the round 10 European Social Survey (ESS, 2022) and Dalia Research (2017). Analysis is conducted using a blockwise regression strategy analyzing how different variables (demographic, psychological, and macroeconomic) affect the attitude towards a tax-based UBI implementation. The study builds on and extends the findings of Roosma & Oorschot (2019) and Vlandas (2021) by using a newer release of the ESS survey and incorporating a macro-level analysis. The main findings suggest that a greater subjective income strain is associated with greater support for a tax-based basic income. Contrary to theoretical expectations, income inequality is negatively associated with UBI support, a finding vanishing when adjusting for purchasing power across the countries. The effect of age on UBI support is mixed across the data sources while individuals with more egalitarian and solidarity-based values express higher support. Clearly stating that the basic income would be financed by taxation lowers the level of support, contradicting Meltzer & Richard (1981) and suggesting that individuals may suffer from “fiscal illusion”.
Keywords: UBI Universal Basic Income Rational Choice Theory Social Welfare